Analisis Kegiatan Pembiasaan Dalam Menumbuhkan Karakter Disiplin dan Tanggung Jawab Siswa SD Negeri 6 Selong Melalui Kegiatan Imtaq dan Pentas Seni - Silvi Diah Ayu Nurkumala Hadi; Arif Rahman Hakim; Faizah; Baiq Abidaturrosida (Mataram University, 2026)
Character education has become an important aspect of elementary education, as schools are expected to develop not only students' academic achievement but also positive character values. Habituation activities are considered one of the effective strategies to instill discipline and responsibility through continuous practice in students' daily school life. This study aims to analyze the implementation of habituation activities through the IMTAQ (Faith and Piety) program and Arts Performance in fostering discipline and responsibility among students at SD Negeri 6 Selong. A descriptive qualitative research method was employed, with data collected through observation, interviews, and documentation. The research subjects included the principal, teachers, and students of SD Negeri 6 Selong. The results indicate that: (1) IMTAQ activities held every Friday morning, including Qur'an recitation, communal prayer, short religious talks, and Duha prayer, consistently build time discipline and religious responsibility; (2) Arts Performance activities, carried out through scheduled rehearsals and periodic performances, cultivate discipline, commitment, and a sense of responsibility toward individual roles and group tasks; and (3) supporting factors include teacher commitment, principal support, and student enthusiasm, while inhibiting factors include inconsistent parental support and limited time allocation. This study concludes that habituation activities through the IMTAQ and Arts Performance programs are effective in sustainably fostering discipline and responsibility among elementary school students.